ASSESSMENT OF NUTRITIONAL STATUS OF ADULTS WITH CARDIOVASCULAR DISEASES - NEETA PATTAN; AAFIYA IFFATH (The Journal of Research ANGRAU, 2026)
The study was conducted in 2024 to assess the nutritional status, food habits and management of CVD among adults. A purposive random sampling method was employed to select respondents.Based on the study’s objective, a suitable, pre-structured questionnaire was designed to collect information. The questionnaire comprised socio-demographic data, anthropometric data, biochemical parameters, clinical signs and symptoms, dietary data, diagnosis and treatment and management of CVD. Hundred participants residing in Bengaluru, within an age group of 40 to 65 years with cardiovascular complications were included in the research. The data collected was analysed through statistical analysis as a percentage, standard deviation and chi-square test. The majority of the respondents (86%) were of the age group between 40 59 years. The data on the education levels of the respondents revealed that 44 percent of them were graduates and the majority of the respondents (64%) were from the nuclear family. The family history of cardiovascular diseases revealed that 54 percent of respondents were with no family history. Most of the respondents (54%) were overweight followed by 22 percent of the respondents who were in the obese class I category indicating a prevalence of obesity among the respondents. Being physically inactive is recognized as one of the most significant risk factors for CVD which strongly supports the results. A higher number of the respondents (53%) were non vegetarians and 53 percent and 48 percent of them were with diabetes and hypertension respectively. The elevated levels of triglycerides and LDL with low levels of HDL might be the strong link for the development of CVD. Seventy nine percent of the respondents had Coronary Artery Disease (CAD) and heart failure and had undergone angioplasty and Coronary Artery Bypass Grafting (CABG). Non vegetarians (52%) had a maximum occurrence of CAD compared to other types of diet, however, the P value indicated that there was no statistically significant association between the type of diet and occurrence of CVD. The chi-square test indicated that there is no statistically significant association between BMI and CVD (since P is 0.234 > 0.05) even though the obese respondents had a higher percentage of cardiovascular disease.